PENTINGNYA ATTITUDES TOWARDS PURCHASING GREEN FOOD PRODUCTS, SOCIAL NORMS, DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP INTENTIONS TO PURCHASE GREEN FOOD PRODUCTS - Prananta, Widya; Wijaya, Angga Pandu; Febriatmoko, Bogy (Bisnis-Net, 2024)
Switching to environmentally friendly products can help minimize adverse environmental impacts and provide health benefits. Consumers buy organic food because they consider it safer than conventional food. This research aims to explore the influence of Attitudes Towards Green Products, Social Norms, and Perceived Behavioral Control on Intentions to Purchase Green Food Products. The Theory of Planned Behavior (TPB) provides a theoretical framework for predicting and understanding consumer behavior, accounting for three factors—attitude, subjective norms, and perceived behavioral control—and integrating them into a conceptual model. This theory implies that consumer behavior is a clear expression of their intentions.cQuantitative research methods were used to collect data from a representative sample of the population of Semarang. The sample for this research consists of consumers who use environmentally friendly food products in Semarang and were selected through screening questions. A total of 125 respondents participated in this research. The data obtained will be tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results are expected to provide insight into the importance of Attitudes Towards Green Products and Perceived Behavioral Control in forming beliefs and intentions to buy environmentally friendly food products, while social norms cannot influence a person's intention to buy environmentally friendly food products.